Адміністративна дигіталізація: розвиток правових засад дигіталізації виконавчої влади в 2003-2013 роках (історико-правовий екскурс) - Наджафлі, Е. М.; Nadzhafli, E. M. (Європейські перспективи. - 2024. - № 2. - С. 350-357, 2024)
Статтю присвячено історико-правовому аналізові специфіки процесу дигіталізації виконавчої влади в сучасній Україні протягом 2003 – 2013 років, з виокремленням основних правових закономірностей такого процесу. Доведено, що основними правовими особливостями цього етапу дигіталізації виконавчої влади були: запровадження електронної інформаційної системи «Електронний Уряд», із затвердженням переліку і порядку надання інформаційних та інших послуг з використанням електронної інформаційної системи «Електронний Уряд»; започаткування процесу надання адміністративних послуг в електронній формі; створення правових засад поступового переходу документообігу в органах виконавчої влади на електронну (цифрову) форму, яка стала рівнозначною з паперовою формою документообігу; започаткуавння формування Реєстру інформаційних, електронних комунікаційних та інформаційно-комунікаційних систем органів виконавчої влади; запровадження елементів електронної форми нормотворчості в органах виконавчої влади; інституціалізація електронних запитів на доступ до публічної інформації; початок переходу системи адміністративних послуг, що надаються органами виконавчої влади, на рейки електронного формату; запровадження системи електронної взаємодії органів виконавчої влади. З’ясовано роль і місце Концепції розвитку електронного урядування в Україні 2010 року, в якій були вперше закріплені дефініції електронного урядування та електронного уряду, а також окреслені пріоритетні напрямки дигіталізації виконавчої влади на перспективу.

The article is devoted to the historical and legal analysis of the specifics of the process of digitization of the executive power in modern Ukraine during 2003-2013, with the main legal regularities of such a process being highlighted. It is shown that the dominant paradigm of this stage of digitalization of the executive power, laid as the basis of the legal strategy of digitalization, became the ideology of statecentrism, which exalted the role of the state in the implementation of the digitalization course, turned society into a passive recipient of state initiatives brought down from above, and also downplayed the role and importance of human rights. Such a paradigm could not be a stable legal basis for the successful completion of digitalization as a legal process, caused the «fragility», half-heartedness and incompleteness of many positive initiatives and achievements in this direction, and soon had to cause a revision of its ideological and conceptual foundations. It has been proven that the main legal features of this stage of digitalization of the executive power were: the introduction of the electronic information system «Electronic Government», with the approval of the list and order of providing information and other services using the electronic information system «Electronic Government»; starting the process of providing administrative services in electronic form; creation of the legal basis for the gradual transition of document circulation in the bodies of executive power to electronic (digital) form, which has become equivalent to the paper form of document circulation; initiation of the formation of the Register of information, electronic communication and information and communication systems of executive authorities; introduction of elements of the electronic form of rule-making in the bodies of executive power; institutionalization of electronic requests for access to public information; the beginning of the transition of the system of administrative services provided by the executive authorities to the rails of the electronic format; introduction of a system of electronic interaction of executive authorities. The role and place of the 2010 concept of e-governance development in Ukraine, in which the definitions of e-governance and e-government were fixed for the first time, as well as the priority directions of digitization of the executive power for the future, were clarified.

Дан историко-правовой анализ специфики процесса дигитализации исполнительной власти в современной Украине в период 2003 – 2013 годов, с выделением основных правовых закономерностей такого процесса.
Administrative digitalization: development of the legal principles of executive authority digitalization in 2003-2013. (historical and legal excursion)
Keywords: дигіталізація; система виконавчої влади; органи виконавчої влади; державне управління; адміністративна реформа; історико-правовий аналіз; digitalization; system of executive power; bodies of executive power; state administration; administrative reform; historical and legal analysis; дигитализация; система исполнительной власти; органы исполнительной власти; государственное управление; административная реформа; историко-правовой анализ